Use of beacon technology to control cattle behavior - А.Х. Сукут; А.Б. Закирова; A.B. Жаныс (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2021)
The article is mostly devoted to the study of the possibilities of using modern information technologies in animal husbandry to identify and monitor the behavior and welfare of cows. Since the work associated with dairy herd management also implies the economic pressure felt by breeders, numerous efforts have been made to create a new method that would be worthy of competition when compared to current solutions. According to the authors’ opinion, the method of collecting and processing data using radio beacons, as well as data storage, allows for identifying the behavior and physiological conditions of a dairy herd more fully. It is equally important to note the price competitiveness of this method. Since the data is collected in large quantities, it was decided to abandon the processing of the data on the local computer and instead use the cloud computing engine. The presented information system creates a sequence of components that have been tested, both at the level of creation and at the level of research. The research results were compared with academic knowledge from literary sources. It should be noted that part of the validation of the above methodology was the comparison of the results that had been achieved during the study using a pedometer. The main goal of this article is to develop a new method in the field of information technology and a method based on beacons, which are quite versatile devices, using data stores that allow identifying the behavior and physiological state of dairy cattle, methods that would be competitive compared to existing solutions, especially for the price. In the proposed solution, there were used both information coming from microcomputers and weather forecast data coming from meteorological stations, which simplify the above identification.